An Effect Of Company Size, Profitability and Financial Leverage on Earnings Response Coefficient (Empirical Study of Mining Companies Listed on The Indonesi Stock Exchange in 2019-2021) - Hernadianto Hernadianto; Viranita Yolanda (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
Earnings Response Coefficient is one of the methods used to determine the extent of the relationship between stock returns and earnings. Earnings Response Coefficient as a material for estimating stock returns when reacting to reported earnings. The purpose of this study was to determine the effect of company size, profitability and financial leverage on the earnings response coefficient of mining companies on the Indonesia Stock Exchange in 2019-2021. The population in this study amounted to 63 companies. While the samples obtained were 22 companies. The sampling technique uses a purposive sampling technique, the research method is a quantitative method. Data analysis used was descriptive statistics, classical assumption test, and multiple linear regression analysis using SPSS 26. The results showed that firm size had an effect on ERC with a significant value of 0.014<0.05, Profitability had an effect on ERC with a significant value of 0.007<0 .05, financial leverage has no effect on ERC with a significant value of 0.255> 0.05. Meanwhile, company size, profitability and financial leverage have a joint effect on ERC with a significant value of 0.010 <0.05.